Fe3O4@carbon@zeolitic imidazolate framework-8 nanoparticles as multifunctional pH-responsive drug delivery vehicles for tumor therapy in vivo. Issue 46 (28th October 2015) - He, Mengni; Zhou, Jiajia; Chen, Jian; Zheng, Fangcai; Wang, Dongdong; Shi, Ruohong; Guo, Zhen; Wang, Haibao; Chen, Qianwang
Abstract : Controlled drug release is a promising approach for cancer therapy due to its merits of reduced systemic toxicity and enhanced antitumor efficacy. Abstract : Controlled drug release is a promising approach for cancer therapy due to its merits of reduced systemic toxicity and enhanced antitumor efficacy. Here, multifunctional Fe3 O4 @carbon@zeolitic imidazolate framework-8 (FCZ) hybrid nanoparticles (NPs) were successfully constructed. Owing to the porosity and acid-sensitivity of zeolitic imidazolate framework-8 (ZIF-8), FCZ NPs not only displayed an improved drug loading capacity compared to most of the polymeric nanocarriers, but also exhibited excellent pH-triggered release of doxorubicin (DOX) in vitro . Moreover, carbon dots (CDs) embedded in the porous carbon shell and superparamagnetic iron oxide nanocrystals could simultaneously function as intracellular fluorescence imaging and T 2 *-weighted magnetic resonance imaging (MRI) contrast agents, respectively. The results obtained from the MTT assay demonstrated good biocompatibility of FCZ NPs. DOX release experiments showed pH regulation-dominated drug release kinetics: a weak acidic pH in tumor areas could trigger sustained drug release, suggesting that FCZ NPs are ideal drug delivery systems. Moreover, the remarkable inhibition of tumor growth without side effects was confirmed in vivo. These results provide convincing evidence establishing the multifunctional FCZ NPs as promising candidates for tumor therapy.